Human conscious response to thermal input is adjusted to changes in mean body temperature. Issue 3 (23rd January 2008) - Flouris, A D; Cheung, S S
Abstract : Objective and Design: To detect the dependable criteria of behavioural thermoregulation through modelling temperature fluctuations of individuals allowed to freely manipulate inlet water temperature of a liquid conditioning garment (LCG) during 130 min of passive exposure to −20°C interspersed with a 10 min period of moderate exercise at the 65th minute using a double-blind experiment. Participants: Eleven volunteers (5 women; 23.40 (SD 2.09) years; BMI: 23.24 (SD 2.19)) who lacked previous experience with LCG and cold exposure experiments. Results: Despite variations in core and skin temperatures, thermal comfort, thermal sensation, and mean body temperature did not fluctuate significantly over time. Participants were able to find a desired level of LCG inlet temperature within 25 minutes which was maintained at similar levels until the 65th minute of the cold exposure. During exercise, LCG inlet water temperature decreased significantly. Regression models demonstrated that mean skin temperature and change in mean body temperature were significantly associated with thermal comfort and thermal sensation. Subsequent models revealed that, although all temperature variables were associated with LCG inlet water temperature, the coefficient of determination mainly depended on mean skin temperature and change in mean body temperature. The involvement of skin temperature was anticipated as the liquid conditioning garment was in contact with the skin. Conclusions: Humans generate conscious thermoregulatory responses in resting and exercise conditions during exposures to cold environments that are aimed towards maintaining a threshold mean body temperature, rather than temperature changes in individual body regions.